Description of a new species of clupeid fish, Amblygaster indiana (Clupeiformes: Clupeidae), off Eraviputhenthurai, west coast of India - Mary, Anthonipillai Arockia; Balasubramanian, Thngavelu; Selvaraju, Shanker; Shiny, Anthonipillai (Zootaxa, 2017)
A new species, Amblygaster indiana sp. nov., is described from 12 specimens collected from fish landing centers and fish markets at Eraviputhenthurai, west coast of India. The new species can be differentiated from all other species of Amblygaster by its larger size and very deep body, 8 circular-shaped pre-pelvic scutes, different gill rakers counts, large eyes, 40 lateral scales, and peculiar gap between the left and right frontoparietal striae on the top of the head. The new species has been seasonally captured with A. sirm in Eraviputhenthurai and also other coastal waters of the south west coast of India. The proportions of A. indiana sp. nov. and A. sirm in fish catches are approximately 1 to 20. Gillnets and shore seines are used to catch Amblygaster spp. along the Eraviputhenthurai coast and along the coastal zones of south west coasts of India.